Comparison of sodium hydroxide and calcium hydroxide pretreatments of giant reed for enhanced enzymatic digestibility and methane production. (November 2017) - Jiang, Danping; Ge, Xumeng; Zhang, Quanguo; Zhou, Xuehua; Chen, Zhou; Keener, Harold; Li, Yebo
Highlights: Sodium hydroxide and calcium hydroxide pretreatments of giant reed were compared. Revenue from sodium hydroxide (NaOH) pretreatment can't offset the chemical input. Calcium hydroxide (Ca(OH)2 ) pretreatment improved glucose yield and methane yield. Pretreatment with 7% Ca(OH)2 had a positive net benefit of $5.8/tonne dry biomass. Ca(OH)2 is more feasible than NaOH for improving biogas production from giant reed. Abstract: NaOH pretreatment with leachate reuse and Ca(OH)2 pretreatment were compared for improved enzymatic digestibility and biogas production from giant reed, a promising energy crop. The NaOH pretreatment with leachate reuse increased glucose yields during enzymatic hydrolysis by 2.6-fold, and methane yields during anaerobic digestion by 1.4- to 1.6-fold. However, NaOH pretreatment had a negative net benefit (i.e., revenue from increased energy production minus chemical cost). Pretreatment with 7–20% Ca(OH)2 not only improved glucose yield and methane yield by up to 2.3-fold and 1.4-fold, respectively, but also obtained a net benefit of $1.1–5.8/tonne dry biomass. Thus, Ca(OH)2 pretreatment was shown to be more feasible than NaOH pretreatment for biogas production from giant reed.